Invasive prenatal diagnosis in Poland. Postulates of modification of the medical infrastructure - Głusiec, Waldemar (Polish Journal of Public Health, 2013)
The implemented invasive prenatal diagnosis (IPD) in Poland includes three procedures of obtaining biological material of the fetus (amniocentesis, chorionic villus sampling, percutaneous umbilical cord blood sampling) and its biochemical, cytogenetic and molecular analysis. This enables a reliable verification of several thousands of genetic defects, and in consequence leads to planning appropriate care and treatment of the child. Unfortunately, the invasive prenatal diagnosis may turn out to be deadly for the fetus and may cause health loss of the pregnant woman. Sadly, all invasive procedures include risks of life or health loss.Another important ethical issue is the frequent use of the unfavorable diagnosis as a basis for a legal termination of the pregnancy. The aim of the article is to remind the conditions, necessary for an ethical conduction of the IPD and the establishment of the directions in the Polish invasive diagnostics that will lead to a true “humanization of medicine”. The plane on which the analysis will be conducted is the ontological personalism, characterized by epistemological and ethical realism. In this perspective, the basic criterion for the moral judgment is the integral wellbeing of the person. IPD is thus ethical, when its main goal is to aid the unborn child and its mother. The postulates of each stage of the diagnosis can be summarized in four general orders: ensuring access to the test, taking maximum precautions, physicians’ empathy, integration of therapy and palliative care.